GENETIC ASSESSMENTS OF SOME LOCAL AND IMPORTED GENOTYPES OF RICE IN SULAIMANI GOVERNORATE - IRAQ - Hamma-Umin, Bestoon.; Hama-Ali, E. O. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was carried out at two locations in Sulaimani Governorate, Iraq during 2022 to investigate the genetic potential of thirty-one rice genotypes to highlights the genetic diversity among rice genotypes and emphasizes the importance of considering both genetic and environmental factors in rice breeding programs. The distinct performance of genotypes across different traits and locations provides valuable information for selecting and developing rice varieties with improved characteristics and higher yield potential. The results of the analysis of variance indicate highly significant differences among the genotypes for all studied traits at both Chalakh and Penjwen locations. This suggests a substantial genetic diversity among the studied genotypes, shows their potential as valuable genetic resources for breeding programs. Additionally, the interaction between genotypes and environments was found to be highly significant for most traits, emphasizing the importance of considering both genetic and environmental factors in rice research. G1 was superior to the other genotypes regarding the grain yield plant-1 with 60.909 and 29.004 g at Chalakh and Penjwen locations respectively. Moreover, the impact of location on the studied traits was significant, with Chalakh outperforming Penjwen in all traits. This difference in performance could be attributed to variations in climatic conditions and environmental factors between the two locations.